A research study in the motivation and employee satisfaction in the China’s private university system - Zhang, Siyu (2022)
Teachers are the transmitters of cultural knowledge and play a key role in the development of the younger generation. As powerful agents of civilisation, teachers' job satisfaction deserves widespread attention, but has not been much studied in China. This is especially true given the specific nature of private universities in China, where the number of teachers in this group is increasing year by year. Therefore, Organisations need to pay attention to teachers' job motivation and satisfaction and find appropriate motivational approaches by exploring the relationship between the two. In this dissertation, five motivational factors, namely pay, promotion, supervision, co-worker and work itself, were selected by reviewing motivation theories to discuss the correlation with job satisfaction. A quantitative approach was adopted to collect data and analyse them through a questionnaire administered to private university teachers in China. A comparison with previous theories revealed that job satisfaction is complex and is influenced by a combination of factors. The data revealed that the overall level of job satisfaction among Chinese private university teachers was high and that intrinsic motivation was more important than extrinsic motivation. At the same time, this study found no statistically significant correlation between age and gender and job satisfaction.